Pibid as a pedagogical strategy in initial teaching education - Dominschek, Desire Luciane; Alves, Tabatha Castro (Universidade Estadual de Campinas, 2017)
This study analyzes the impact of the Institutional Program of Initial Teaching Scholarship (PIBID) on basic education at national level. The PIBID is a Brazilian public policy that encourages and values the improvement in teacher training for basic education. The main goal of this study is to investigate the program'saction in teacher training, as well as to analyze how the initial teacher education is being conducted. It was decided to describe the PIBID and present the performance data of the program through the years of 2007 to 2013, in order to illustrate the benefits of the Program. As a research source, the studies of Gatti, Pimenta, Saviani, Severino and Tardif were used. Based on the documentary analysis of the guidelines 738/2007, 122/2009, 096/2013, public notice 719/2013, Decree 7.219 / 2010, Management Report (2009-2013) andManagement Report (2009-2014), the results presented reveal a structured public policy that values and strengthens teacher education, improves quality in public schools, integrating universities and schools, provides the continuing education of professors from the colleges and of school supervisors.